A low-cost, mobile real-time kinematic geolocation service for engineering and research applications. (October 2021) - Broekman, André; Gräbe, Petrus Johannes
Graphical abstract: Highlights: Successful realisation of a low-cost RTK-grade geolocation service. Digital twinning of both modern and historically significant assets. Mobile acquisition unit incorporating high level customizability. Low cost and wide serviceability area for multidisciplinary research. Abstract: Centimetre accurate geolocation service is beneficial to a wide range of applications, ranging from sports engineering, civil infrastructure, autonomous vehicles, surveying to digitisation of historically significant structures. Previously, these features were confined to prohibitively expensive commercial hardware, requiring technical knowledge and experience to operate. Continued technological advancements have seen the miniaturisation of electronics and antennas, coupled with an increase in the number and performance of global navigation satellite systems (GNSS) by various nations and organisations, providing global signal coverage. This paper demonstrates a low-cost, mobile, real-time kinematic (RTK) geolocation service for engineering and research applications, fabricated from components readily available from commercial suppliers. This solution, consisting of a mobile RTK base station and RTK rover, provides centimetre-accuracy performance up to a distance of 15 km away from the base station. Correction data is transmitted over the internet using free and open software solutions. The small footprint of both the RTK base station and RTK rover, provides versatile applications even in remote locations. The performance of the geolocation service is validated using field experiments, comparing measurements against state-of-the-art photogrammetry, light detection and ranging (LiDAR) and digital level measurement technologies. The authors encourage the adoption of the RTK geolocation solution based on the calibrated results.